Desenvolvimento de software – estudo de caso do sistema APAC Barros Barreto - PAES, Eliwelton Gomes (2019)
The present work presents the development (specification, implementation and evaluation) of a WebApp tool, whose objective is to perform, in a computerized way, the process of requesting the Authorization of High Complexity Ambulatory Procedure (APAC) from the University Hospital João de Barros Barreto (HUJBB). The system development process involved the preparation of three specification documents, prior to system implementation: requirements specification, analysis specification and design specification. The tool resulting from the development process seeks to aid and optimize the process of requesting these procedures, through a unique area for creating and printing forms in the standard accepted by the Unified Health System (SUS).